2007
DOI: 10.1002/rcm.3086
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of multiple bioactive constituents in Rheum tanguticum Maxim. ex Balf. by high‐performance liquid chromatography coupled to tandem mass spectrometry

Abstract: A simple, rapid method was developed using on-line high-performance liquid chromatography (HPLC)-diode array detection (DAD)/electrospray ionization mass spectrometry (ESI-MS) to simultaneously analyze multiple bioactive constituents in the extract of Rheum tanguticum Maxim. ex Balf. (Dahuang), a traditional Chinese medicine (TCM). Many bioactive constituents gave prominent [M-H]- ions in the negative ion ESI mass spectra. Among them, 41 different constituents including 16 anthraquinone derivatives, 7 phenylbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 10 publications
2
39
0
2
Order By: Relevance
“…The elution order of the two isomers was also in agreement with previous reports. [42,43]. Meanwhile, a major ion at m/z 227 was also observed, which was identical with the [M−H] − ion of resveratrol (5), which was further supported by acidic hydrolysis of P. cuspidatum extract (details shown in Supplementary Data).…”
Section: Identification Of Components In P Cuspidatum Extractmentioning
confidence: 73%
“…The elution order of the two isomers was also in agreement with previous reports. [42,43]. Meanwhile, a major ion at m/z 227 was also observed, which was identical with the [M−H] − ion of resveratrol (5), which was further supported by acidic hydrolysis of P. cuspidatum extract (details shown in Supplementary Data).…”
Section: Identification Of Components In P Cuspidatum Extractmentioning
confidence: 73%
“…In the current study, Aloeemodin (Fig. 1A) is a monomer of phenanthrenequinones extracted from rhubarb and has a similar chemical structure with emodin [9]. Several studies have reported the protective effect of emodin against cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that the ion at m/z 225 underwent the successive losses of a methyl group and CO molecule, resulting in ions at m/z 210 and 182. Therefore, compound 29 was reasonably identified as chrysophanol by comparing with the literature data [4,24].…”
Section: Characterization Of Flavonoidsmentioning
confidence: 99%